Activation of serotonergic 5-HT1A receptors in the lateral parabrachial nucleus increases NaCl intake - De Gobbi, JIF; Barbosa, S. P.; De Luca, L. A.; Thunhorst, R. L.; Johnson, A. K.; Menani, José Vanderlei [UNESP] (Elsevier B.V., 2005)
Previous studies using non-specific serotonergic agonists and antagonists have shown the importance of serotonergic inhibitory mechanisms in the lateral parabrachial nucleus (LPBN) for controlling sodium and water intake. In the present study, we investigated whether the serotonergic 5-HTIA receptor subtype in the LPBN participates in this control. Male Holtzman rats had cannulas implanted bilaterally into the LPBN. Bilateral injections of the 5-HTIA receptor agonist, 8-hydroxy-2-(di-n-propylamino) tetralin (8-OH-DPAT, 0.1, 1.25, and 2.5 mu g/ 0.2 mu l), into the LPBN enhanced 0.3 M NaCl and water intake of rats injected subcutaneously with the diuretic furosemide (10 mg/kg bw) and a low dose of the angiotensin-converting enzyme inhibitor, captopril (5 mg/kg bw). The increase in NaCl intake produced by 8-OH-DPAT injections was reduced in dose-related manner by pre-treating the LPBN with the selective 5-HTIA serotonergic antagonist, WAY-100635 (WAY, I and 2 mu g/0.2 mu l). In contrast, WAY did not affect water intake produced by 8-OH-DPAT. WAY-100635 injected alone into the LPBN had no effect on NaCl ingestion. Injections of 8-OH-DAPT (0.1 mu g/0.2 mu l) into the LPBN also increased 0.3 M NaCl intake induced by 24-h sodium depletion (furosemide, 20 mg/kg bw plus 24 h of sodium-free diet). Serotonin (5-HT, 20 mu g/0.2 mu l) injected alone or combined with 8-OH-DPAT into the LPBN reduced 24-h sodium depletion-induced 0.3 M NaCl intake. Therefore, the activation of serotonergic 5-HTIA receptors in the LPBN increases stimulated hypertonic NaCl and water intake, while 5-HT injections into the LPBN reduce NaCl intake and prevent the effects of serotonergic 5-HTIA receptor activation. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: serotonin; angiotensin II; fluid and electrolyte balance; NaCl intake; thirst; LPBN